Β decay studies of n-rich Cs isotopes with the ISOLDE Decay Station. (21st March 2017) - Lică, R; Benzoni, G; Morales, A I; Borge, M J G; Fraile, L M; Mach, H; Madurga, M; Sotty, C; Vedia, V; Witte, H De; Benito, J; Berry, T; et al.
Abstract: Neutron-rich Ba isotopes are expected to exhibit octupolar correlations, reaching their maximum in isotopes around mass A  = 146. The odd- A neutron-rich members of this isotopic chain show typical patterns related to non-axially symmetric shapes, which are however less marked compared to even- A ones, pointing to a major contribution from vibrations. In the present paper we present results from a recent study focused on 148–150 Cs β -decay performed at the ISOLDE Decay Station equipped with fast-timing detectors. A detailed analysis of the measured decay half-lives and decay scheme of 149 Ba is presented, giving a first insight in the structure of this neutron-rich nucleus.